Investigation of the influence of determining factors on the efficiency indicators of organizational and technological decisions for the reconstruction of industrial buildings - Kovalov, V. (Ways to Improve Construction Efficiency, 2020)
In the conditions of a limited number of free land for the construction of objects of different functional purpose in many cities, the task of finding territorial reserves becomes increasingly important. Territories of degraded industrial zones may be considered as such reserves. Projects for the reconstruction of industrial buildings with a change in their functional purpose usually involve a complex of works to improve the energy efficiency of buildings and ensure their environmental friendliness, repair of roofs, interior equipment, dismantling or reconstruction of utility networks, etc. Compression conditions should also be taken into account as they impose limitations on the use of productive technology and the technical condition of the objects, according to which they determine the required set of works for the restoration of the structural structures. Given the need to ensure the investment attractiveness of projects for the reconstruction of industrial buildings with a change of functional purpose, further research is needed to develop effective organizational and technological decisions, taking into account specific requirements. Thereby the investigation is dedicated to solving the problem of improving the organization and management of the process of reconstruction of industrial buildings with a change in functional purpose based on the improvement of the method of substantiating organizational and technological desicions aimed at improving energy efficiency and ensuring environmentalitys of objects, taking into account the systemic influence of determining factors. The dependences of the cost of reconstruction of industrial buildings with a change in functional purpose from the systemic influence of determining factors: technical condition, constraint conditions, safety, quality, energy efficiency, environmentality and efficient use are established. The evaluation of the established dependences of the cost of reconstruction of industrial buildings with the change of functional purpose from determining organizational, technological and technical factors according to Fisher's criterion confirmed their adequacy to the studied process. The use of such dependencies makes it possible to search for reserves in order to improve organizational and technological desicions by reducing the risk of adverse destabilizing factors.